Jejak Adventure : Platform Penyedia Traveling Berbasis Web - Pahlefi, Bagus; Ananda, Dahliar (eProceedings of Applied Science, 2023)
Abstract—In this era of highly advanced technology, it has a positive impact on all aspects. One of them is in the tourism aspect. In this case, it is massively that many business opportunities are created because of this impact. One example is the package travel business that makes it easier for people to travel. But also in this convenience, package travel business people or known as travel agents do not all have the quality or experience to facilitate the community. There are even some travel agents who are not responsible for running an package travel business. Therefore, a web platform was created that accommodates experienced and trusted travel agents to make it easier for people to choose package travels safely and comfortably. This application is developed using Laravel framework and MySQL database.Keywords— Tourist, Package Travel, Travel Agent, Laravel,Web,MySql